Differences in the definitions used for esophageal and gastric diseases in different countries - Takubo, Kaiyo; Vieth, Michael; Aida, Junko; Sawabe, Motoji; Kumagai, Yoichi; Hoshihara, Yoshio; Arai, Tomio (Digestion, 2009)
Background: Definitions and opinions in the field of gastroenterology vary widely in different countries. Methods: Here we discuss four such important differences: the definition of the esophagogastric junction (EGJ), the possible precursor of Barrett's adenocarcinoma, the definition of Barrett's esophagus (BE), and the histologic criteria for mucosal adenocarcinoma. In addition, we consider which definitions and opinions might be valid and practical. Results: There are two different endoscopic definitions of the EGJ. Our research on German subjects has indicated that many small Barrett's adenocarcinomas may arise not in the intestinal-type but in the cardiac-type mucosa. If an area of columnar-lined esophagus (CLE) is only partially involved by intestinal metaplasia, then the latter cannot always be demonstrated in biopsy specimens. Therefore, we do not think that a definition of BE as CLE with histologic intestinal metaplasia is practical. Data from the literature have shown that many cases of high-grade dysplasia (HGD) progress to carcinoma within a very short time, and in most such cases the carcinoma has been underdiagnosed in biopsy specimens as HGD. Conclusion: With regard to the definitions and opinions, an exchange of views between gastroenterologists in North America, Europe, and Japan would be desirable. © 2009 S. Karger AG, Basel.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Barrett's esophagus; Dysplasia; high-grade; Esophagogastric junction; Esophagus; columnar-lined; Mucosa; intestinal-type; cardiac-type; Mucosal carcinoma